(untitled) (Materiali di Estetica. Terza serie, 2017)
This article analyses Fulvio Papi’s writings dealing the great literature of the Twentieth Century, and is devoted in particular to his work on Musil, Yourcenar, Pavese. Poetic and literary writing offer to the philosopher a rich field of investigation, concerning themes that also belong to his philosophical research. The following topics are dealt with: the different conditions for the formation of the identity of the subjects; the multifarious quality of time; writing as a form of existence of the Self.